Correlation between Children Respiratory Virus Infections and Climate Factors - Saadi, Souhir; Kallala, Ouafa; Fodha, Imene; Jerbi, Amira; BenHamida-Rebai, Meriem; Ben Hadj Fredj, Mouna; Ben Hamouda, Hichem; Mathlouthi, Jihen; Khlifa, Monia; Boussofara, Raoudha; Boussetta, Khadija; Abroug, Saoussen; Trabelsi, Abdelhalim (Journal of Pediatric Infectious Diseases, 2021)
Objective Respiratory viruses are the most important cause of lower respiratory tract infections (LRTI) in children. Meteorological factors can influence viral outbreaks. The objective of this study was to determine the association between climate variables and respiratory virus detection.Methods Multicenter prospective 1-year surveillance was conducted among children hospitalized for LRTI in Tunisia. Nasopharyngeal aspirates were tested by direct immunofluorescence assay (DIFA) for the detection of respiratory syncytial virus (RSV); adenovirus (AdV); influenza virus (IFV) A and B; and parainfluenza virus 1, 2, and 3 (PIV1/2/3). Samples were further analyzed by reverse-transcription polymerase chain reaction for the detection of human metapneumovirus (hMPV). Monthly meteorological data were determined by consulting the National Institute of Meteorology and the World Weather Online Meteorological Company websites. Pearson's correlation tests were used to determine the statistical association between the detection of respiratory viruses and climatic characteristics.Results Among 572 patients, 243 (42.5%) were positive for at least one virus. The most frequently detected viruses by DIFA were RSV (30.0%), followed by IFVA (3.8%), IFVB (3.5%), PIV (0.9%), and AdV (0.9%). HMPV was detected in 13 RSV-negative samples (3.3%). Dual infections were detected in seven cases (1.2%). Monthly global respiratory viruses and RSV detections correlated significantly with temperature, rainfall, cloud cover, wind speed, wind temperature, and duration of sunshine. Monthly IFV detection significantly correlated with rainfall, wind speed, wind temperature, and duration of sunshine. HMPV detection significantly correlated with temperature and wind temperature.Conclusion Respiratory viral outbreaks are clearly related to meteorological factors in Tunisia.
Keywords: respiratory virus; climatic factor; children; seasonality; lower respiratory tract infection